Chinnamastā, the aweful Buddhist and Hindu tantric goddess - Benard, Elisabeth Anne (Buddhist tradition series, 1994)
On the significance and worship of Chinnamastā (Hindu deity), and Chinnamuṇḍā (Buddhist deity).